In frame fibrillin-1 gene deletion in autosomal dominant Weill-Marchesani syndrome. Issue 1 (1st January 2003) - Faivre, L; Gorlin, R J; Wirtz, M K; Godfrey, M; Dagoneau, N; Samples, J R; Le Merrer, M; Collod-Beroud, G; Boileau, C; Munnich, A; Cormier-Daire, V
Abstract : Weill-Marchesani syndrome (WMS) is a connective tissue disorder characterised by short stature, brachydactyly, joint stiffness, and characteristic eye anomalies including microspherophakia, ectopia of the lenses, severe myopia, and glaucoma. Both autosomal recessive (AR) and autosomal dominant (AD) modes of inheritance have been described and a gene for AR WMS has recently been mapped to chromosome 19p13.3-p13.2. Here, we report on the exclusion of chromosome 19p13.3-p13.2 in a large AD WMS family and show that, despite clinical homogeneity, AD and AR WMS are genetically heterogeneous entities. Because two AD WMS families were consistent with linkage to chromosome 15q21.1, the fibrillin-1 gene was sequenced and a 24 nt in frame deletion within a latent transforming growth factor-β1 binding protein (LTBP) motif of the fibrillin-1 gene was found in a AD WMS family (exon 41, 5074_5097del). This in frame deletion cosegregated with the disease and was not found in 186 controls. This study strongly suggests that AD WMS and Marfan syndrome are allelic conditions at the fibrillin-1 locus and adds to the remarkable clinical heterogeneity of type I fibrillinopathies.